(untitled) (INTEGRATION PROCEEDING, 2023)
Preeclampsia is a complication of pregnancy characterized by an increase in blood pressure at 20 weeks gestation. If not detected and treated immediately it may cause maternal and fetal death, therefore it is necessary to monitor through ANC so that preeclampsia does not worsen in the third trimester of pregnancy. This case study was conducted to provide midwifery care for third trimester pregnant women with preeclampsia at RSUD Dr. H Moch Ansari Saleh Banjarmasin. This study used a case study design on pregnant women selected by purposive sampling. Primary data sourced from patients were taken using the SOAP format. The patient’s preeclampsia was characterized by complaints of headache, heavy neck and swollen legs and there was a family history of preeclampsia. High blood pressure since 39 weeks gestation, BP: 155/99 mmHg, urine protein (+) so that it can be determined as G3P1A1 at 39 weeks gestation with preeclampsia, live single fetus intra uteri. Management provided in the formof deep breath relaxation techniques, warm compresses on the feet, IEC on the prevention of hypertension, initial and continued dose therapy of 40% MgSO4, and nifedipine 10 mg 3x1 per oral. The mother’s preeclampsia problem was successfully resolved on the last day of the progress notes.